2019
DOI: 10.1001/jamanetworkopen.2019.5892
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mineralocorticoid Receptor Antagonist Use With All-Cause Mortality and Hospital Readmission in Older Adults With Acute Decompensated Heart Failure

Abstract: Key Points Question Is use of mineralocorticoid receptor antagonist at discharge associated with better outcomes in patients hospitalized for acute decompensated heart failure? Findings In this cohort study of 2068 propensity score–matched Japanese patients hospitalized for acute decompensated heart failure, mineralocorticoid receptor antagonist administered at discharge was statistically significantly associated with a lower risk for the primary composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 30 publications
9
65
0
Order By: Relevance
“…We collected data on patient demographics, medical history, underlying heart disease, pre-hospital activities, socioeconomic status, signs, symptoms, medications, laboratory tests at hospital presentation, electrocardiogram, echocardiography, and clinical events during the index hospitalization 9,17,18 .…”
Section: Data Collection and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected data on patient demographics, medical history, underlying heart disease, pre-hospital activities, socioeconomic status, signs, symptoms, medications, laboratory tests at hospital presentation, electrocardiogram, echocardiography, and clinical events during the index hospitalization 9,17,18 .…”
Section: Data Collection and Definitionsmentioning
confidence: 99%
“…We set the occurrence of new infection or infection that became obvious after hospitalization as one of the secondary outcomes. The causes of death were classified according to the VARC (Valve Academic Research Consortium) definitions 20 , and were adjudicated by a clinical event committee 9,15,17,18 .…”
Section: Data Collection and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the design and patient enrollment have been described previously [ 8 , 21 , 22 ]. In brief, we consecutively enrolled the patients who had the acute HF symptoms defined by the modified Framingham criteria and who received treatment for heart failure involving intravenous drugs (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] In terms of HFpEF, the TOPCAT trial showed that spironolactone could reduce the rate of hospitalization for HF but not that of cardiovascular death or the composite outcome in stable HFpEF. 5 Although several other studies have provided supportive evidence of MRAs in HFpEF on post hoc analyses, [18][19][20] the drug's precise effect remains inconsistent in the literature. Additionally, there are no studies investigating the impact of MRAs on cardiovascular mortality in acute decompensated HFpEF patients.…”
Section: Introductionmentioning
confidence: 99%